EARLY DIAGNOSIS OF ALZHEIMER’S DISEASE USING DEEP LEARNING AND IMAGE PROCESSING ON BRAIN MRI IMAGES - Barapatre, Harish; Pawar, Nilesh; Mohite, Shweta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
To take preventative action, Alzheimer’s disease (AD) must be identified early. Particularly in those over 60, Alzheimer’s disease is regarded as one of the acute illnesses that kill people. Because of the diversity and complexity of brain tissue, using MRI (Magnetic Resonance Imaging) to classify Alzheimer’s disease is thought to be a challenging process. As a result, the systems for Alzheimer’s disease detection and classifi- cation comprise four stages: MRI pre-processing, segmentation, feature extraction, and classification. The primary goal of the first stage is to remove any noise from medical resonance images (MRIs) that could be caused by light reactions or errors in the imaging medium. The second step involves extracting the region of interest, which is the Alzheimer’s disease zone. To prepare for the classification process, the third stage will involve obtaining and storing MRI image features in an image vector. The fourth stage will then involve the classifier, which will specify the Alzheimer-type picture segmentation, thereby recognizing the disease at an early stage. The hybrid methodology employed in this study blends deep learning-based convolutional neural networks (CNNs) with traditional classifiers such as support vector machines (SVM) and random forests. The interpretabil- ity of traditional classification methods is combined with the advantages of deep learning’s feature extraction capabilities in this framework achieved higher accuracy when compared to the current CNN methods.